Thermodynamic Insights for Electrochemical Hydrogen Compression with Proton-Conducting Membranes - Benjamin L. Kee; David Curran; Huayang Zhu; Robert J. Braun; Steven C. DeCaluwe; Robert J. Kee; Sandrine Ricote (Membranes, 2019)
Membrane electrode assemblies (MEA) based on proton-conducting electrolyte membranes offer opportunities for the electrochemical compression of hydrogen. Mechanical hydrogen compression, which is more-mature technology, can suffer from low reliability, noise, and maintenance costs. Proton-conducting electrolyte membranes may be polymers (e.g., Nafion) or protonic-ceramics (e.g., yttrium-doped barium zirconates). Using a thermodynamics-based analysis, the paper explores technology implications for these two membrane types. The operating temperature has a dominant influence on the technology, with polymers needing low-temperature and protonic-ceramics needing elevated temperatures. Polymer membranes usually require pure hydrogen feed streams, but can compress H <semantics> 2 </semantics> efficiently. Reactors based on protonic-ceramics can effectively integrate steam reforming, hydrogen separation, and electrochemical compression. However, because of the high temperature (e.g., 600 <semantics> ° </semantics> C) needed to enable viable proton conductivity, the efficiency of protonic-ceramic compression is significantly lower than that of polymer-membrane compression. The thermodynamics analysis suggests significant benefits associated with systems that combine protonic-ceramic reactors to reform fuels and deliver lightly compressed H <semantics> 2 </semantics> (e.g., 5 bar) to an electrochemical compressor using a polymer electrolyte to compress to very high pressure.